Corrosion protection study in construction steel armor (Research, Society and Development, 2019)
In this work an alternative is studied the protection against corrosion in the metal frames used in the construction. Metallic structures exposed to weathering can contribute to the degradation of the entire concrete structure of a building, a process called concrete corrosion, which generates huge damage to construction companies and sometimes compromises to the entire structure of A building, being shown in this work a method of protection of the metallic structures of the construction. Conducting a brief review of the literature and experiments, this work shows the efficiency of the protection of steel bars involved with a magnesium tape, having confirmation of efficiency by metallography that show the surface of the metal, and the presence of Chemical species by X-ray diffraction (DRX). It is possible to verify that the results are promising, providing for engineering a path that is not currently researched, involving a range of areas ranging from the large buildings, to the simplest houses, that can have a longer lifespan and with Less maintenance expenses.